2018
DOI: 10.21053/ceo.2017.00857
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nicotine Exposure on Hair Cell Toxicity and Embryotoxicity During Zebrafish Development

Abstract: Objectives Nicotine has various adverse effects including negative impacts associated with maternal exposure. In the current study, we examined nicotine-induced damage of hair cells and embryotoxicity during zebrafish development.Methods Zebrafish embryos were exposed to nicotine at several concentrations (5, 10, 20, and 40 μM) and embryotoxicity were evaluated at 72 hours, including hatching rate, mortality, teratogenicity rate, and heart rate. Hair cells within the supraorbital (SO1 and SO2), otic (O1), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The average number of hair cells in two main regions, the anterior lateral line (ALL) system, including the supraorbital [SO1 and SO2], otic [O1], and occipital [OC1] nerves, and the posterior lateral line (PLL) system, including the neuromasts of the trunk and tail of zebrafishes (p 3–6), was determined using a fluorescence microscope at 7 dpf (LSM5 PASCAL; Carl Zeiss, Germany). 9,17,18,25,27 The hair cells were identified by our two experts, and they were evaluated in all experimental and control conditions (n = 29–40 for each of the concentrations)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average number of hair cells in two main regions, the anterior lateral line (ALL) system, including the supraorbital [SO1 and SO2], otic [O1], and occipital [OC1] nerves, and the posterior lateral line (PLL) system, including the neuromasts of the trunk and tail of zebrafishes (p 3–6), was determined using a fluorescence microscope at 7 dpf (LSM5 PASCAL; Carl Zeiss, Germany). 9,17,18,25,27 The hair cells were identified by our two experts, and they were evaluated in all experimental and control conditions (n = 29–40 for each of the concentrations)…”
Section: Methodsmentioning
confidence: 99%
“…The toxic effect of E-cig usage during pregnancy has been also addressed; the results demonstrated that the nicotine consumed during the use of E-cigs is similar to that consumed during conventional cigarette smoking. 8 Numerous animal studies have confirmed the toxic effects of nicotine to the developing fetus; 9,10 the effects of nicotine exposure by E-cig usage during fetal development is suggested to be similar to those by conventional cigarette smoking. 8,11 However, the constituents and potential adverse effects of E-cigs are not well understood; 3,11,12 moreover, there is a dearth of scientific information pertaining to the hazards of these substances to gestational development and sensory hair cells.…”
Section: Introductionmentioning
confidence: 99%
“…To study the effect of pH on different drug conditions, four commonly used drugs of abuse were selected for this study. Nicotine (Sigma-Aldrich) was administered at a concentration of 5 µM (García-González et al, 2020;Petzold et al, 2009;Yoo et al, 2018), morphine sulphate (Sigma-Aldrich) was administered at 2.6 µM (Lopez-Luna et al, 2017), d-amphetamine (Sigma-Aldrich) was administered at 22 µM (Irons et al, 2010), and caffeine (Tocris) was administered at 200 µM (Gutiérrez et al, 2020). Concentrations were based on a combination of larval and adult zebrafish studies investigating effects on locomotor activity.…”
Section: Pharmacological Agentsmentioning
confidence: 99%
“…4 Research has shown that upon cell entry through nicotinic acetylcholine receptors (nAChRs), Nic can induce apoptosis in a variety of cell types, including lung epithelial cells. 5,6 Although lung epithelial cells are not classic phagocytes, they are the first line of defense against invading microorganisms and are involved in bacterial uptake and clearance. 7,8 Moreover, a role for lung epithelial cell apoptosis has been demonstrated in the development and progression of COPD.…”
Section: Introductionmentioning
confidence: 99%